2011
DOI: 10.1523/jneurosci.0336-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Copper Reduces A  Oligomeric Species and Ameliorates Neuromuscular Synaptic Defects in a C. elegans Model of Inclusion Body Myositis

Abstract: Alzheimer's disease and inclusion body myositis (IBM) are disorders frequently found in the elderly and characterized by the presence of amyloid-␤ peptide (A␤) aggregates. We used Caenorhabditis elegans that express A␤ in muscle cells as a model of IBM, with the aim of analyzing A␤-induced muscle pathology and evaluating the consequences of modulating A␤ aggregation.First, we tested whether the altered motility we observed in the A␤ transgenic strain could be the result of a compromised neuromuscular synapse. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 73 publications
3
31
0
Order By: Relevance
“…In our study, glucose gradually induced Aβ oligomerization accompanied by decrease in Aβ monomers. These results are in agreement with previous studies where carbohydrate-rich diets accelerated the neurodegeneration by increasing Aβ oligomers [467,468], and reduction in Aβ oligomerization resulted in improved disease pathology [57,411,515]. In our study, we also found that administration of 2DOG reduced disease pathology by decreasing Aβ oligomerization.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, glucose gradually induced Aβ oligomerization accompanied by decrease in Aβ monomers. These results are in agreement with previous studies where carbohydrate-rich diets accelerated the neurodegeneration by increasing Aβ oligomers [467,468], and reduction in Aβ oligomerization resulted in improved disease pathology [57,411,515]. In our study, we also found that administration of 2DOG reduced disease pathology by decreasing Aβ oligomerization.…”
Section: Discussionsupporting
confidence: 93%
“…ACh neurotransmission is essential for muscle contraction, but increased ACh levels can result in paralysis due to muscle overexcitation. As a result, Aβ expression can provide resistance to cholinergic agonists such as aldicarb, that increases synaptic levels of ACh, or levamisole, that increases ACh receptor sensitization [411,529]. Aldicarb resistance is used as an indication of pre-synaptic defects whereas resistance against both aldicarb and levamisole is used as an indication of post-synaptic defects [417].…”
Section: Discussionmentioning
confidence: 99%
“…The deletion of the msra-1 gene heightens the locomotory impairments of Ab transgenic worms Muscle expression of Ab causes locomotory impairments in C. elegans (40,56). To test the relevance of oxidation repair in this model of IBM, we first evaluated locomotion in a transgenic strain that carries a deletion of the msra-1 gene (allele tm1421) and expresses the human Ab peptide in muscle cells.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, Ab seems to specifically affect the subtype of nicotinic acetylcholine receptors that are sensitive to nicotine but insensitive to levamisole (40,56). These receptors are closely related to the a7-nicotinic acetylcholine receptor, proposed to be associated with Ab 1-42 neurotoxic effects in mammals (55,59).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation